Aplikasi Sistem Pakar Berbasis Mobile Untuk Diagnosis Dini Meningitis - Mona Pradipta Hardiyanti; R. Rizal Isnanto; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2017)
In Indonesia, cases of meningitis happen quite a lot because meningitis patients are not aware that he was infected with meningitis. This is because the early symptoms resemble regular headaches. Lack of community information about a disease and its symptoms and causes make the process of treatment is slow so it can make the disease worse and fatal. This research is devoted to makes of meningitis expert system that can be used by the public to solve the problem. This expert system is developed using Expert System Development Life Cycle (ESDLC). The steps to create an expert system using this method are assessment, acquisition of knowledge, design, and testing. This application tested using black box testing methods and directly testing by an expert. Based on test results showed a qualitative testing that system there is no error of its functions. Application of expert system can make the process of diagnosis according to the data obtained from the experts. For renew of disease and symptoms, it can be done by modifying the database.